Розвиток обслуговуючих кооперативів як засіб збільшення мережі робочих місць на селі - Решитько, Т. В.; Rcshitko, Т. (КНТУ, 2013)
Стаття присвячена розгляду питань взаємозв’язку розвитку обслуговуючих кооперативів на селі із зайнятістю сільського населення. The article discloses the research of interrelationship between development of service-oriented cooperatives in rural areas and increasing job-placement for villagers. The article shows how the development of service-oriented cooperatives in rural areas may influence the organization of considerable quantity of job-placement for village population. The world’s best experience of cooperative movement in rural area was given. It has been pointed out that service-oriented cooperatives provide their members with services at cost-price, improve the conditions of their activity, prevent extracting revenues from agricultural sphere to dealers’ commercial structures. But most importantly they solve social issues while creating job-placement and providing income for villagers. To make a conclusion we may state that development of agricultural service-oriented cooperatives in Ukraine will stimulate the increase of job-placement.
Development of service-oriented cooperatives as a way of increasing job-placement in rural areas
Keywords: сільськогосподарський обслуговуючий кооператив; зайнятість сільського населення; створення нових робочих місць; agricultural service cooperative; rural employment; creating new jobs